BIOCHEMICAL CHANGES IN BETEL QUID CHEWERS AND NON-CHEWERS OF KAKKARAI, THANJAVUR DISTRICT OF TAMILNADU - RAMYA M; ANURADHA R (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Betel quid chewing is ancient, socially acceptable habit in India. AÂ mixture of betel leaf, areca nut and tobacco chewing is used in many parts of India.Â The aim of our study is to assess the biochemical changes of mixture of betel leaf, areca nut and tobacco users.Â A toal of 25 male patients aging â‰¥ 45 years.Â Among then 5 had no habit of chewing betel quit with or without tobacco and 20 possessed the habit for betel quid chewing. A significant difference in biochemical levels among control and chewers.Â The level of plasma glucose, serum enzymesÂ like Alanine Amino Transferase (ALT), Aspartate Amino Transferase (AST), Alkaline phosphatase (ALP), serum cholesterol, HDL- cholesterol , triglycerides urea and creatinineÂ wereÂ found to be increased andÂ the protein level was decreasedÂ chewers when compared to non â€“ chewers. Betel quid chewing is significantly associated with variety of health problems liver markerÂ enzymes, renal marker, lipid profile, glucose in the present study.Â Â Keywords: Betel quid chewers, Non-chewers, Biochemical analysis. Â Key Words : Betel quid chewers , non-chewers, Biochemical analysis.